PEMODELAN MATEMATIKA ALIRAN FLUIDA PADA RADIATOR MOBIL TIPE SR (SINGLE ROW) - Brahmanto, Juanda; Fatahillah, Arif; Dafik, Dafik (Department of Mathematics Education , University of Jember, 2017)
Abstract. Radiator is heat exchanger which used in the cooling system of inside combustion engine, especially car and motorbike, but there are many tipe are used in airplane engine with piston and train engine. In car and motorbike engine, radiator use a liquid as cooler which this liquid will absorb heat from engine cylinder until head cylinder, next the liquid will flow into radiator to be cooled using outside air and if the liquid temperature is decrease, it will be pumped back to engine. This research is to create a mathematic modelling about fluid flow inside a radiator car with single row type. Mathematic model which created is a differential equation based on phisic law in two dimension. The force which effected in this radiator is a initial temperature, velocity of fluid, and viscousity of the fluid. The equation which used in this model is mass equation. Keyword : Radiator, Mathematic Modelling, Mass Equation